Spontaneous neoplasia in captive syngnathid species: A retrospective case series (2003–2014) and literature review. Issue 8 (18th June 2020) - Denk, Daniela; Verin, Ranieri; Ressel, Lorenzo; Lewis, Eleanor; Stidworthy, Mark F
Abstract: Syngnathidae (seahorses, pipefish and seadragons) are charismatic species commonly kept in commercial aquaria, but published literature on syngnathid diseases is limited and immunohistochemical techniques not routinely employed. A retrospective review of 2, 541 syngnathid submissions received between March 2003 and October 2016 identified 18 neoplasms including germ cell tumours, exocrine pancreatic and intestinal carcinomas, chromatophoromas, and single cases of lymphoma, thyroid and renal carcinoma, swim bladder and pituitary adenoma. Big‐bellied seahorses accounted for 19% of submissions, but 50% of neoplasms were diagnosed in this species. This study includes the first reported cases of germ cell tumours, chromatophoroma, thyroid carcinoma and pituitary adenoma in Syngnathidae and the first reports of neoplasia in pipefish species. Out of nine commercial antibodies trialled for immunohistochemical characterization of neoplastic tissue, only pan‐cytokeratin proved cross‐reactive. Electron microscopy was performed in four cases. Tumours should be considered as differential diagnosis in cases with buoyancy issues, debilitated or emaciated animals, and may predispose to secondary infections. This study highlights the value of histopathological disease surveillance for commercial aquarium settings.